PENGARUH MANAJEMEN KARIR DAN MOTIVASI KARIR TERHADAP KARIR PADA GURU DI KABUPATEN LEBAK - Yumhi Yumhi (Universitas La Tansa Mashiro, 2016)
This research is intended to look for factors related to teacher career. This study uses quantitative associative surveys using correlational analysis techniques, which aim to know the general description of the relationship of career management style and career motivation to career. The study population was all teachers of Madrasah Tsanawiyah YAUMIN Kabupaten Lebak, which amounted to 34 teachers. The sample of the study is part of the study population, which amounted to 34 teachers taken by using Boring Sampling.In this study there are two independent variables, namely career management style and career motivation that has a direct positive relationship to career.Referring to the results of this study can be concluded that the career will be achieved maximally if enhanced career management style and fit with career motivation.